Limited-view multi-source quantitative photoacoustic tomography. (6th May 2015) - Gao, Hao; Feng, Jing; Song, Liang
Abstract: A limited-view scheme is proposed for multi-source quantitative photoacoustic tomography (MS-QPAT), in which the acoustic measurements following each optical illumination are acquired on the partial boundary near the optical source instead of the entire boundary, namely the limited-view MS-QPAT. The proposed limited-view scheme has an improved signal-to-noise ratio when the data are measured near the optical source, and reduces the acquisition time of the imaging system with a single or limited-view acoustic detector. A limited-view MS-QPAT example is to acquire acoustic data following each of 90 optical illuminations, in contrast to acoustic data for each of 90 optical illuminations under the conventional MS-QPAT setting. However, due to the incomplete data, the initial acoustic pressure can no longer be stably reconstructed that serves as an intermediate step in the conventional two-step reconstruction that first reconstructs the initial acoustic pressure and then the optical coefficients. Therefore the direct reconstruction of optical coefficients is considered using the coupled opto-acoustic forward model. The reconstruction algorithm is based on the quasi-Newton method, i.e. limited-memory BFGS with efficient adjoint computations of objective function gradients, and the sparsity-regularized formulation is also considered with tensor framelet sparsity transform and solved by the alternating direction method of multipliers.